Canonical meaning of legal term «title» - MICHOWICZ, PRZEMYSŁAW (Prawo Kanoniczne, 2018)
The main aim of the present paper was to determine correctly legal significance of the term «title». The research started by analyzing the roman law, specifically those fragments which confirmed the doctrine’s intuition concerning the fact that the strictly legal connotation of the term should be dated under the regime of Diocletian. It was also highlighted that the Code of Canon Law 1983 uses the notion in different meanings from which the most researched was this, which embraces all legal categories, included those existing in spoken legal language. Eventually, three dimensions of commercium iuridicum: matrimonial, the ones related to an idea of liability and propriety, were indicated as abstract models containing a possible definition of the concept.